Pelatihan PBB (Peraturan Baris Berbaris) oleh Dosen, Pembina dan Taruna Akademi Kelautan Banyuwangi di SMK NU Sudirman Rogojampi Banyuwangi - Alfi Khoiruman, Muhamad; Satriyo, Galih; Rohamn, Saiful; Ahmad, Fandi; Istiari, Nina Ruly; Pratiwi, Yosi Mulyana; Ningrum, Nadiya Lifa; Irawan, Doni Hadi; Suwarso, Suwarso; Janoko, Janoko; Nurdian, Yudhi Harris (Universitas Pahlawan Tuanku Tambusai, 2024)
Discipline is one of the key aspects in shaping students' character, especially in vocational school environments. The drill training (Peraturan Baris Berbaris or PBB) by lecturers, instructors, and cadets from the Academy of Maritime Banyuwangi at SMK NU Sudirman Rogojampi Banyuwangi aims to improve students' discipline, teamwork, and responsibility through structured activities. This study uses a qualitative descriptive method with data collection techniques including observation, interviews, and documentation to evaluate the effectiveness of this training program. The results show that the PBB training enhances students' ability to follow rules, improves teamwork skills, and fosters a more disciplined character. The discussion of the research links the findings with previous studies, which indicate that discipline-based training is effective in developing students' non-technical (soft) skills that are relevant to the needs of the workforce. The conclusion of this study is that PBB training not only provides practical benefits in improving student discipline but also contributes to strengthening character education overall. The collaboration between higher education institutions and secondary schools has also proven to be effective in providing a holistic learning experience for students.